Formulation and Bioequivalence Evaluation of a Miniaturized Fexofenadine Hydrochloride Tablet - Woo-Yul Song; Chang-Soo Han; Won-Sang Yu; Jae-Won Jang; Gyoung-Won Kim; Yoo-Shin Jeon; Young-Jin Kim; So-Jeong Jeong; Ji-Hyun Kang; Dong-Wook Kim; Yun-Sang Park; Chun-Woong Park (Pharmaceutics)
Background: Fexofenadine hydrochloride (FEX) is widely used to treat allergic rhinitis. However, poor solubility, high cohesiveness, and risk of polymorphic transformation present significant formulation challenges. Conventional FEX tablet formulations are large and may pose swallowing difficulties for patients with dysphagia. Therefore, a miniaturized FEX tablet that maintained bioequivalence with the marketed product was developed. Methods: An organic solvent-based binder and porous carrier enhanced solubility, flowability, and process efficiency. The formulation was optimized using a design of experiments approach to assess the effects of tablet size and porous carrier incorporation on dissolution and residual solvent content. Scale-up feasibility was evaluated using Froude number-based process optimization, and stability studies were conducted under accelerated conditions (40 °C and 75% relative humidity) to ensure long-term formulation robustness. Results: The miniaturized tablet exhibited dissolution at pH 4.0 and pH 6.8 equivalent to that of the reference product, whereas a faster dissolution rate was observed at pH 1.2. No significant changes were observed in the dissolution rate, crystalline structure, or impurity levels over six months. An in vivo bioequivalence study demonstrated that the test formulation met the bioequivalence criteria, with 90% confidence intervals for the area under the curve and the Cmax falling within the regulatory acceptance range. Conclusions: A miniaturized and commercially viable fexofenadine hydrochloride tablet was developed (44% weight reduction and 50% volume reduction compared to the marketed product). The organic solvent-based binder and porous carrier system improved manufacturing efficiency, stability, and solubility, thereby ensuring compliance with regulatory standards. These findings provide valuable insights into size reduction, solubility enhancement, and large-scale production strategies for the development of future pharmaceutical formulations.